Why Do People Demand Rent Control? - Daniel Müller; Elisabeth Gsottbauer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We conduct a representative survey experiment in Germany to understand why people support inefficient policies. In particular, we measure beliefs about and preferences for rent control - a policy that is widely regarded as harmful by experts. To tease out causal mechanisms, we provide randomly selected subsets of participants with empirical estimates about the effects of rent control on rent prices and housing supply and with information about the consensus among economists against rent control. We find that people update their beliefs and that this leads to lower demand for rent control. Left-wingers update their beliefs more strongly, which reduces the ideological gap in support for rent control by about one-third. Providing information about economists' rejection of this policy leads to the largest reduction in support. However, the main drivers of support for rent control are fairness considerations and profit motives. Our study also highlights the importance of trust in expert advice since treatment effects are consistently larger among those who indicate trust in expert advice. Finally, an obfuscated follow-up survey conducted three weeks later reveals that the effects, both on support for rent control and on beliefs, persist only for those who trust.
Keywords: H10; H30; H31; 330; beliefs; demand for bad policies; housing supply; rent control; survey experiment; trust in experts